2023
DOI: 10.3390/pharmaceutics15010161
|View full text |Cite
|
Sign up to set email alerts
|

Copaiba Oil-Loaded Polymeric Nanocapsules: Production and In Vitro Biosafety Evaluation on Lung Cells as a Pre-Formulation Step to Produce Phytotherapeutic Medicine

Abstract: Copaiba oil has been largely used due to its therapeutic properties. Nanocapsules were revealed to be a great nanosystem to carry natural oils due to their ability to improve the bioaccessibility and the bioavailability of lipophilic compounds. The aim of this study was to produce and characterize copaiba oil nanocapsules (CopNc) and to evaluate their hemocompatibility, cytotoxicity, and genotoxicity. Copaiba oil was chemically characterized by GC-MS and FTIR. CopNc was produced using the nanoprecipitation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In addition, the peak at 1697 and 1646 cm −1 suggests carbonyl stretching. Moreover, the peaks at 1447, 1380, and 887 cm −1 indicate the bending vibrations of aliphatic CH2, C-O bond vibrations, and C=C bending, respectively [12,21]. The PLDLA/NR infrared spectrum presented the main bands of both individual polymers (PLDLA and NR).…”
Section: Fourier-transform Infrared Spectroscopymentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, the peak at 1697 and 1646 cm −1 suggests carbonyl stretching. Moreover, the peaks at 1447, 1380, and 887 cm −1 indicate the bending vibrations of aliphatic CH2, C-O bond vibrations, and C=C bending, respectively [12,21]. The PLDLA/NR infrared spectrum presented the main bands of both individual polymers (PLDLA and NR).…”
Section: Fourier-transform Infrared Spectroscopymentioning
confidence: 97%
“…In addition, the peak at 1697 and 1646 cm −1 suggests carbonyl stretching. Moreover, the peaks at 1447, 1380, and 887 cm −1 indicate the bending vibrations of aliphatic CH 2 , C-O bond vibrations, and C=C bending, respectively [12,21]. are composed of long chains of poly(cis-1,4-isoprene), and due to such properties, they provide increased malleability and flexibility to the PLDLA due to its elastomeric features.…”
Section: Fourier-transform Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The poly(acrylic acid) (PAA)-protected platinum nanoparticles (PAA-Pt) proved to be efficient scavengers of free radicals like peroxyl radicals, superoxide anions, and hydroxyl radicals [ 85 ]. An imbalanced oxidative status due to the production of ROS can be reduced by the presence of antioxidants such as PtNPs [ 86 ]. The research of Watanabe, et al demonstrated that these nanoparticles can be used in the treatment of diseases related to oxidative stress and ageing because these platinum nanoparticles have activity like mitochondrial electron transfer complex I [ 85 ].…”
Section: The Main Categories Of Commonly Used Nanopharmaceuticalsmentioning
confidence: 99%